Challenges of implementing electronic government procurement : a case study on Bangladesh water development board - Alam, Syed Rafiqul (BRAC University, 2013)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.